Active Flow Control for Aerospace Operations by means of a Dense Wireless Sensor and Actuator Network - Robles, Ramiro (2016)
Work in Progress Session, IEEE conference on Emerging Technologies and factory Automation (EFTA2016). 6 to 9, Sep, 2016. Berlin, Germany.